2019
DOI: 10.1128/jcm.00961-19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oxacillin and Cefoxitin Disk Diffusion and Microbroth Dilution Methods for Detecting mecA -Mediated β-Lactam Resistance in Contemporary Staphylococcus epidermidis Isolates

Abstract: Methicillin (β-lactam) resistance in Staphylococcus epidermidis is mediated by the mecA gene, with resistance reported to be as high as 90%. The goal of this study was to evaluate oxacillin and cefoxitin disk diffusion (DD) and broth microdilution (BMD) methods for the detection of mecA-mediated β-lactam resistance in 100 human isolates of S. epidermidis (48 mecA-positive isolates and 52 mecA negative isolates). Oxacillin DD tests using the Clinical and Laboratory Standards Institute (CLSI) M100-S28 breakpoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…In some studies, it has been reported that the sensitivity of the latex agglutination method using cefoxitin disc is between 88% and 100%, and specificity is between 97% and 100% in determining methicillin resistance in Staphylococcus. 12,[20][21][22]25 In our study, the sensitivity of the latex agglutination method was found to be 80.9% and specificity was found to be 70.2% in all Staphylococcus isolates. Only in S. aureus isolates, the sensitivity and specificity rates were 100% and 80%, respectively, and 76.3% and 68.6% for general coagulase-negative Staphylococcus, respectively.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…In some studies, it has been reported that the sensitivity of the latex agglutination method using cefoxitin disc is between 88% and 100%, and specificity is between 97% and 100% in determining methicillin resistance in Staphylococcus. 12,[20][21][22]25 In our study, the sensitivity of the latex agglutination method was found to be 80.9% and specificity was found to be 70.2% in all Staphylococcus isolates. Only in S. aureus isolates, the sensitivity and specificity rates were 100% and 80%, respectively, and 76.3% and 68.6% for general coagulase-negative Staphylococcus, respectively.…”
Section: Discussionsupporting
confidence: 46%
“…In some studies, it has been reported that the sensitivity of the disk diffusion test using cefoxitin disc is between 94% and 100% and the specificity is between 96% and 100% for determining methicillin resistance in Staphylococcus. [19][20][21][22][23][24] When the PCR result is taken as a reference in this study, the sensitivity of the disk diffusion method in all Staphylococcus isolates was 100% and specificity was determined to be 45.9%. Considering the highest number of isolated Staphylococcus in the study, the sensitivity of the disk diffusion method was 100% for all the isolates; also it was determined that the specificity rates varied between 14.3% and 61.1% (median: 47.4% [IQR: 16.3%]).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the ability of this species to form biofilms, treatment can be complicated (5) and may require protracted courses of antimicrobials. Furthermore, S. epidermidis isolates often display resistance to many classes of antimicrobials, including the beta-lactams (6).…”
mentioning
confidence: 99%
“…In this issue, Naccache et al detail experiments that they used to evaluate phenotypic methods and breakpoints to determine mecA-mediated methicillin resistance in contemporary clinical S. epidermidis isolates (6). Methicillin resistance has been observed in up to 90% of S. epidermidis isolates which may demonstrate heteroresistance (6,13). Therefore, accurate knowledge of the AST profile, including the presence or absence of mecA, is clinically important.…”
mentioning
confidence: 99%
“…In addition, 69.1% of the NAS isolates also exceeded the cut-off for penicillin resistance (69.1%) and, surprisingly, 97.4% of NAS also exceeded the limit for oxacillin. Naccache et al [ 67 ] previously reported about the capability of S. epidermidis to carry methicillin resistance. Furthermore, the oxacillin and penicillin resistance of NAS is also in line with Cheng et al [ 34 ], who reported that NAS were 84% resistant against oxacillin followed by 62% against penicillin.…”
Section: Discussionmentioning
confidence: 99%